2021
DOI: 10.15407/fz67.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Analysis of Sciatic Nerve in Mice With Peripheral Neuropathy After Transplantation of Adipose-Derived Multipotent Mesenchymal Stromal Cells

Abstract: We investigated the peripheral demyelination in transgenic mice with peripheral neuropathy and the effect of adiposederived multipotent mesenchymal stromal cells (ADSCs) transplantation on the ultrastructural features of the sciatic nerve in these mice. The B6.Cg-Tg(PMP22)C3Fbas/J transgenic mice with peripheral neuropathy were injected intramuscularly with ADSCs, which were isolated from the adipose tissue of FVB-Cg-Tg(GFPU) mice transgenic by GFP. For ultrastructural analysis, tissue fixation in animals was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Other studies have shown that implantation of SCs derived from AD-MSCs showed improved musculoskeletal function [ 36 ] as well as decreased neuronal damage [ 37 ]. Earlier in the morphological study [ 18 ] it was shown that transplantation of AD-MSCs into mice with peripheral neuropathy of the sciatic nerve causes a thickening of the myelin sheath of axons and an increase in the number of lamellae. These results are consistent with reports of enhanced sciatic nerve regeneration by restoring the myelin sheath and axons of peripheral nerves in mice with peripheral neuropathy after MSCs transplantation [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have shown that implantation of SCs derived from AD-MSCs showed improved musculoskeletal function [ 36 ] as well as decreased neuronal damage [ 37 ]. Earlier in the morphological study [ 18 ] it was shown that transplantation of AD-MSCs into mice with peripheral neuropathy of the sciatic nerve causes a thickening of the myelin sheath of axons and an increase in the number of lamellae. These results are consistent with reports of enhanced sciatic nerve regeneration by restoring the myelin sheath and axons of peripheral nerves in mice with peripheral neuropathy after MSCs transplantation [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in the morphological study was shown that in mice with sciatic nerve neuropathy induce both thickening of the myelin sheath and increase in the number of lamellae, after AD-MSCs transplantation. In this way, in mice with hereditary peripheral neuropathy, AD-MSCs transplantation has a protective effect on the ultrastructural features of the sciatic nerve and inhibits the process of axonal demyelination [ 18 ].…”
Section: Introductionmentioning
confidence: 99%